Modelos, lenguajes y abstracción (ING) - Sánchez, José Aurelio (Uniciencia, 2008)
Every construction process (whatever buildings, machines, software, etc.) requires first to make a model of the artifact that is going to be built. This model should be based on a paradigm or meta-model, which defines the basic modeling elements: which real world concepts can be represented, which relationships can be established among them, and son on. There also should be a language to represent, manipulate and think about that model. Usually this model should be redefined at various levels of abstraction. So both, the paradigm an the language, must have abstraction capacity. In this paper I characterize the relationships that exist between these concepts: model, language and abstraction. I also analyze some historical models, like the relational model for databases, the imperative programming model and the object oriented model. Finally, I remark the need to teach that model-driven approach to students, and even go further to higher level models, like component models o business models.